Studying the risk of anemia in patient with chronic diabetes (Eurasian Journal of Research, Development and Innovation, 2024)
Patients with DM2 and anemia were those with high body mass,hypertension ,increased waist circumference ,and longer time of the disease. This set of changes characterizes the anemia as chronic disease,which has a significant adverse effect on quality of life of diabetic patients and is associated with the progression of the disease; the development of comorbidities significantly contributes to the increased risk of cardiovascular disease. However, against what was expected, the results of blood glucose were higher in non anemic patients, which is contradictory due to the anemia of these patients being associated with an inflammatory condition, for being characterized as normocytic normochromic anemia